Priority Variables for Handling Slum Settlements Based on the Tourism Village Concept in Sedau, Singkawang City - Palupi, Santi; Krisnaputri, Nilam Atsirina; Adrianus, Bernard (Jurnal Penelitian Pariwisata, 2024)
The issue of slum settlements in Singkawang City has garnered government attention, with Sedau identified as the third priority area for intervention. However, many revitalization efforts fail due to mismatched methods that do not consider environmental, social, and economic characteristics. This study aims to identify priority variables for addressing slum settlements based on the concept of developing a tourism village to improve residents' quality of life and support local economic development. The research method employed is expert judgment through the Analytical Hierarchy Process (AHP), which helps evaluate relevant variables. The findings reveal four main priority variables: good accessibility, a unique tourism village concept, provision of clean water, and waste management. These findings provide important insights for decision-making in planning interventions. Recommendations are directed at the government, development sectors, and the Sedau community, emphasizing the need for better planning, particularly regarding accessibility and infrastructure such as roads, water supply, and waste management. The study also notes its limitations to provide context for the generalization of results and to guide future research. Keywords: planning, slum settlement, tourism village, tourism